ChemInform Abstract: Site‐Selective Electrophilic Cyclization and Subsequent Ring‐Opening: A Synthetic Route to Pyrrolo[1, 2‐a]quinolines and Indolizines. Issue 6 (20th February 2013) - Aggarwal, Trapti; Kumar, Sonu; Dhaked, Devendra K.; Tiwari, Rakesh K.; Bharatam, Prasad V.; Verma, Akhilesh K.
Abstract Treatment of alkynylated pyranoquinolines such as (III) and (VI) with AgOTf or I2 is found to allow a new, facile, and efficient access to biologically important pyrroloquinolines.